Stealthy Path Planning Using Navigation Meshes - Mendonça, Matheus R. F.; S. Bernardino, Heder; Fonseca Neto, Raul (2015 Brazilian Conference on Intelligent Systems, 2015)
Stealth-based path finding focuses on finding a path between two points that minimizes the agent's exposure to patrolling units. This problem arises in the robotics field and in modern games, in which an agent must traverse the terrain covertly. This paper presents a real-time method capable of finding a covert path in a terrain patrolled by multiple moving agents using a special navigation mesh. The generated path passes through cover whenever possible in order to avoid open areas and reduce its overall visibility. Also, the stealthy agent uses different movement speed based on the current area it traverses. It is considered here that the environment is known and static.